Empirical model for estimating the surface roughness of machined components under various cutting speed - JO Osarenmwinda (Journal of Applied Sciences and Environmental Management)
The increasing importance of turning operations is gaining new dimensions in the present industrial age, in which the growing competition calls for all the efforts to be directed towards the economical manufacture of machined parts as well as surface finish is one of the most critical quality measure in mechanical products. In the present work, empirical models for estimating the surface roughness of machined components under various cutting speed have been developed using regression analysis software. The centre lathe was used to turn the components (stainless steel, mild steel and aluminum cast) at different cutting speed ranging between 76 rev/min to 600 rev/ min at a constant depth of cut of 1 mm/pass and feed rate of 0.5 mm/rev. and surface roughness of machined components measured with a digital portable surface roughness tester (TR100 Model) using centre line average method. The values obtained from the empirical models were found to compare favourably with the experimental values. The Mean Absolute Percent Deviation (MAPD) which measures absolute error as a percentage was found to be 1.46% (stainless steel), 4.55 %( mild steel) and 4.76% (aluminum cast) respectively. These values were insignificant and below the maximum recommended value of 10%. These model performances were therefore found to be satisfactory and show good predictability. @JASEM